Reiner Aktivismus? Politisierung von Literatur und Kunst im postsowjetischen Russland - Meindl, Matthias (2018)
How did the resurgence of authoritarian statehood lead to the development of ›art activism‹ by Vojna and Pussy Riot? How did Limonov's aestheticist project of the National Bolshevik Party become a protest movement that aestheticizes politics and expresses social marginality? How did leftist institutional experiments like the artist group Chto Delat emerge despite the repressive conditions in Putin's Russia? Matthias Meindl has been investigating the careers of individual actors ›the political‹ in Russian art and literature since the 1990s. This thesis was accepted by the Faculty of Philosophy of the University of Zurich in the spring semester 2014 at the request of the PhD Commission, Prof. Dr. Sylvia Sasse (principal supervisor) and Prof. Dr. Georg Witte, as a dissertation